JOY OF MISSING OUT (JoMO) SEBAGAI GAYA HIDUP BARU GEN Z MAHASISWA FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI JAKARTA - Diandono, Izzulhaq Satrio; Sujarwo; Saipiatuddin (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The phenomenon of Joy of Missing Out (JoMO) has become a new lifestyle in the social dynamics of Gen Z students in the current digital era. Unlike Fear of Missing Out (FoMO), JoMO reflects the satisfaction and tranquility felt by individuals when they choose not to engage in social activities or viral trends. This study aims to describe how JoMO emerges as a new lifestyle among Gen Z students at the Faculty of Social Sciences, Universitas Negeri Jakarta, and to identify the factors that drive its adoption. This research uses a qualitative descriptive method with data collection techniques through questionnaires and literature studies. The results show that some students have adopted the JoMO lifestyle by reducing meaningless social involvement, focusing on themselves, and choosing activities that support productivity and mental health. The driving factors include fatigue from social pressure, the desire for a more peaceful life, and limiting exposure to social media.